2020
DOI: 10.3389/fphar.2020.590614
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Endovascular Calyx Related Enzymes in Endothelial Dysfunction and Diabetic Vascular Complications

Abstract: In recent years, the number of diabetic patients has rapidly increased. Diabetic vascular complications seriously affect people’s quality of life. Studies found that endothelial dysfunction precedes the vascular complications of diabetes. Endothelial dysfunction is related to glycocalyx degradation on the surface of blood vessels. Heparanase (HPSE), matrix metalloproteinase (MMP), hyaluronidase (HYAL), hyaluronic acid synthase (HAS), and neuraminidase (NEU) are related to glycocalyx degradation. Therefore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 131 publications
(210 reference statements)
0
8
0
Order By: Relevance
“…The three main factors reported to result in glycocalyx degradation in diabetes are reactive oxygen species (ROS), advanced glycation end products and sheddase activation. Both ROS and advanced glycation end products depolymerize hyaluronan, causing a damage in the glycocalyx integrity, while sheddases, like hyaluronidase, heparinase, metalloproteinase and neuraminidase, cleave glycocalyx components (Figure 3) (117). Notably, all these factors are increased in plasma of diabetic patients, which indicates a strong correlation between glycocalyx damage and insulin resistance (118)(119)(120).…”
Section: Endothelial Glycocalyx Damage and Its Link To Risk Factors O...mentioning
confidence: 98%
“…The three main factors reported to result in glycocalyx degradation in diabetes are reactive oxygen species (ROS), advanced glycation end products and sheddase activation. Both ROS and advanced glycation end products depolymerize hyaluronan, causing a damage in the glycocalyx integrity, while sheddases, like hyaluronidase, heparinase, metalloproteinase and neuraminidase, cleave glycocalyx components (Figure 3) (117). Notably, all these factors are increased in plasma of diabetic patients, which indicates a strong correlation between glycocalyx damage and insulin resistance (118)(119)(120).…”
Section: Endothelial Glycocalyx Damage and Its Link To Risk Factors O...mentioning
confidence: 98%
“…Several studies reported the ability of matrix metalloproteinases (MMP) to cleave syndecans, an essential component of proteoglycans. For example, MMP-9, which commonly causes SDC-1 degradation, or MMP-2, that induces the cleavage of SDC-4 [54]. It seems that the action of MMPs is facilitated by the loss of HS.…”
Section: Endothelial Glycocalyx and Sepsismentioning
confidence: 99%
“…Furthermore, low molecular hyaluronic acid fragments produce the expression of vascular cell-adhesion molecule -1 (VCAM-1) and intercellular-adhesion molecule -1 (ICAM-1), resulting in increased macrophage activity, as well as inflammation and endothelial cell damage [57]. These processes may be modulated by the activation of extracellular heparanases by proinflammatory cytokines [54]. Particularly in humans, the endo-β-glucuronidase Heparanase-1 (Hpa-1) is decreased during sepsis and has been proposed as a biomarker to predict the risk of sepsis in adults [58].…”
Section: Endothelial Glycocalyx and Sepsismentioning
confidence: 99%
“…ADAMs can cleave syndecans, one of the major constituents of eGCX, cytokine receptors, and cell adhesion molecules expressed by endothelial cells and leukocytes ( 14 ). As to heparanase, it is capable of degrading heparin sulfate moieties, further aggravating the disruption of eGCX ( 13 , 15 ). According to the study by Schmidt, et al., eGCX degradation involves the specific loss of heparin sulfate caused by endothelial stored heparanase, a TNF-α–responsive, heparin sulfate–specific glucuronidase ( 12 ).…”
Section: The Role Of Egcx In Lung Diseasesmentioning
confidence: 99%